Transformasi Kesenjangan Digital Multi-Level: Analisis Akses, Literasi Strategis, dan Dampak pada Kinerja Akademik Mahasiswa NTT - Maria Florentina Rumba; Valencia Bonaventura Ina Atawolo; Vinsensius More Nggori; Yuliana Logi Tukan; Indrianingsih Chandra (Yayasan Literasi Sains Indonesia, 2025)
This study investigates the multi-layered digital divide among university students in East Nusa Tenggara (NTT), a region characterized by significant geographical and socioeconomic disparities. Utilizing a mixed-methods approach involving surveys and interviews across various NTT universities, the research examines the digital divide across three levels: Access (Level 1), Skills (Level 2), and Outcome (Level 3). The findings reveal that the primary Level 1 barrier is not device ownership, but rather the poor reliability and high cost of internet access, which is largely dictated by uneven geographical infrastructure distribution. At Level 2, students demonstrate high proficiency in basic operational skills (e.g., office software) but exhibit significant weaknesses in higher-order digital literacy, particularly in digital security, information credibility assessment, and strategic academic usage. Crucially, the Level 3 gap is defined by a significant disparity in outcome, where the aspiration for using technology for productivity and self-development ranks highest, yet the actual capacity for advanced strategic functions remains the lowest, underscoring a fundamental gap between awareness and practical empowerment. This study confirms that the digital divide in NTT is a shift from access to strategic capability, demanding targeted policy interventions focused on network equity and advanced digital literacy training.